Innovation in rural areas – methods to improve the quality of citizens life - Luminița Creineanu (Sasu); Liviu Mărcuță (Journal of Research and Innovation for Sustainable Society)
Innovation in rural development and how it has influenced the increase in the quality of life of the rural population has always been a challenge. Innovation can be addressed through the interventions implemented within the measures and intervention areas of the rural development programs and through certain types of projects. New products, practices, and processes represent engines for innovation and diversification of agricultural activities, as well as for improving the competitiveness of the rural economy. The policy tool to support local needs, in reducing economic and social imbalances and urban-rural disparities and promoting innovation is the LEADER approach that encourages small-scale innovative actions in all aspects of rural life (economic, social and environmental). With the help of the information taken and analyzed from the websites of institutions with a role in the elaboration, management, implementation, and control of rural development programs in Romania, projects were identified that encourage innovation through the activities of local action groups at the LEADER rural area level, financed during 2014 – 2020, the beneficiaries of these projects, the value of the contracts and their impact on the rural population. Following the analysis, we want to see which type of projects the innovation took shape and if they helped the evolution of the rural community concretely.